Home Truths : A Deep East Texas Memory - Duff, Gerald (Book collections on Project MUSE., 2011)
Novelist Gerald Duff grew up both in Polk County, in Deep East Texas, and in Nederland, near the Gulf Coast, two drastically different areas in terms of social and economic status, and the way they interact. These communities shaped the way Duff thought and lived, causing him to build up certain false personae to fit in with the crowd. These changes and more are described within the pages of Duff's new memoir, Home Truths: A Deep East Texas Memory. From dealing with intrusive family members to judgmental classmates to marital bliss and misery, Duff's memoir describes situations familiar to any.